Dietary inflammatory potential, genetic predisposition, and incidence of Crohn’s disease and ulcerative colitis - Ji-Mei Gu; Miao Zhao; Jie Zhu; Hao-Wei Tao; Xiao-Ping Shao; Li-Qiang Qin; Yang-Yang Ge; Guo-Chong Chen (Nutrition & Metabolism)
Abstract Background Evidence for a potential link between dietary inflammatory potential and inflammatory bowel disease is limited, and the moderating role of genetic susceptibility remains to be assessed. Objective To evaluate energy-adjusted dietary inflammatory index (E-DII) for the associations with incident Crohn’s disease (CD) and ulcerative colitis (UC) and the role of genetic susceptibility. Methods A total of 205,706 UK Biobank participants who were aged 39–72 years and had no known CD or UC at baseline (2006–2010) were included. The E-DII score was calculated based on energy-adjusted average intakes of 33 food or nutrient items derived from up to five 24-hour dietary recalls. Multivariable Cox regression models were used estimate hazard ratios (HRs) with 95% confidence interval (CI) for incident CD and UC. Results During a median 12.3 years of follow-up, 382 incident CD and 798 incident UC cases were ascertained. A higher E-DII score was not associated with risk of CD (HR Q4 VS. Q1 = 1.28, 95% CI: 0.94–1.74; P-trend = 0.09) or UC (HR Q4 VS. Q1 = 1.10, 95% CI: 0.90–1.36; P-trend = 0.17). There was an interaction between the E-DII and the polygenic risk score (PRS) for CD on incident CD (P-interaction = 0.023), with an association only among participants with a high PRS (HR Q4 VS. Q1 = 1.64, 95% CI: 1.03–2.61) (P-interaction = 0.023). As compared with the participants with a low PRS for CD and a low E-DII score, participants with high levels of both scores had a particularly higher risk of CD (HR = 3.12; 95% CI: 1.74–5.60). Conclusions The association of dietary inflammatory potential with incident CD appears to be amplified by high genetic susceptibility to CD.